Active virological surveillance in backyard ducks in Bangladesh: detection of avian influenza and gammacoronaviruses. Issue 4 (3rd July 2020) - Parvin, Rokshana; Kabiraj, Congriev Kumar; Mumu, Tanjin Tamanna; Chowdhury, Emdadul Haque; Islam, Mohammad Rafiqul; Beer, Martin; Harder, Timm
ABSTRACT: Domestic waterfowl play an important role in the perpetuation and transmission of avian pathogens including avian influenza viruses (AIV) of low and high pathogenicity, which pose severe economic and public health concerns in Bangladesh. This study focused on active surveillance of several avian viral pathogens with a special reference to AIV in selected backyard duck populations in Bangladesh. A total of 500 pooled oropharyngeal and cloacal samples from individual ducks of four districts were tested by real time PCRs for the presence of AIV, avian avulavirus-1, anatid herpesvirus-1, avian parvovirus, avian bornavirus and avian coronavirus. The investigation identified 27 (5.4%) ducks positive for AIV and 12 (2.4%) positive for avian coronavirus. In 13 samples, RNA specific for AIV H4N6 was detected. Phylogenetic analysis of the AIV haemagglutinin H4 and neuraminidase N6 genes suggested a clustering of Bangladeshi AIV H4N6 in Eurasian lineage group 2. Other AIV positive samples had very low virus loads (Cq > 36) and were not subtyped. Coronaviral sequences of a fragment of the polymerase gene were related to Eurasian-Australian duck gamma-coronaviruses. Our current active surveillance in free-range domestic backyard ducks in Bangladesh failed to detect highly pathogenic (HP) AIV in contrast to our previous passive monitoring study. Nevertheless, active monitoring of domestic duck populations may be important to highlight presence and transmission dynamics of economically less important AIV that still may serve as reassortment partners for the generation of new HP and zoonotic AIV. RESEARCH HIGHLIGHTS Active surveillance for viral pathogens in domestic free-range backyard ducks. Detection of avian influenza virus subtype H4N6. First identification of avian gammacoronavirus in ducks in Bangladesh.